Overview of Eating Behavior, Physical Activity, and Parental Obesity History in Relation to Obesity Incidence Among Medical Students at Universitas Muslim Indonesia - Ahyar, Muammar; Makmun, Armanto; Surdam, Zulfiyah; Hidayati, Prema Hapsari; Murfat, Zulfitriani; Hamsah, Muhammad (Newinera Publisher, 2025)
Obesity is a global epidemiological problem that poses a threat to world public health, the Word Health Organization annually publishes that obesity is the cause of death of 2.8 million people. Low physical activity is an important predictor of obesity, besides that the family environment has a big influence on the incidence of obesity in a person. The purpose of the study was to determine the description and relationship of eating behavior, physical activity, and parental obesity history with the incidence of obesity. Methods This study is an analytical descriptive study with a cross sectional method, data were collected once from each participant and analyzed with SPSS using the chi-square test. The results revealed that there were 50 umi medical faculty students who were obese, with poor eating behavior as many as 34 people or 68%, less physical activity as many as 36 people or 72%, obese father's obesity status as many as 33 people or 66% and obtained obese mother's obesity status as many as 30 people or 60%. Data analysis shows that there is a relationship between eating behavior and the incidence of obesity in UMI medical students, there is a relationship between physical activity and the incidence of obesity in UMI medical students, and there is a relationship between a history of parental obesity and the incidence of obesity in UMI medical students. Based on the results obtained, it is concluded that eating behavior, physical activity, and a history of parental obesity are one of the factors that cause obesity in UMI medical students.